REORGANIZATION OF HEALTH PROBLEMS IN RUSSIA - V. A. Alexeev; K. N. Borisov (Модернизация, инновация, развитие, 2016)
General world public health system reorganization trend is its state financing and regulation plus state guarantees for everybody to get free medical aid with focus to preventive treatment. As per World Health Organization, it is the Primary Medical and Sanitary Aid (PMSA) that should be intensively introduced to every country’s health system, since it provides real possibilities to make this system more accessible for everybody and more just. Heath system and PMSA reorganization approaches practiced in many countries are described and assessed. Proceeding from the aim of preserving and strengthening the nation’s health, it is unpromising to reorganize Health System in Russia on the basis of paid medical services and total voluntary medical insurance, since paying capacity of most of its population is low. Effectiveness of the primary medical aid may be increased through creation of infrastructure of so-called General Doctors Practices on the basis of existing network of policlinics. The potential of this network is sufficient for PMSA structural reorganization, but its internal organizational system should be optimized.